An integrative approach to species discrimination in the Eupelmus urozonus complex (Hymenoptera, Eupelmidae), with the description of 11 new species from the Western Palaearctic. (October 2014) - AL KHATIB, FADEL; FUSU, LUCIAN; CRUAUD, ASTRID; GIBSON, GARY; BOROWIEC, NICOLAS; RASPLUS, JEAN‐YVES; RIS, NICOLAS; DELVARE, GÉRARD
Abstract The systematics of the European species of Eupelmus (Eupelmus) Dalman (Hymenoptera: Eupelmidae) belonging to the 'urozonus‐complex' is elucidated through combined molecular and morphological characterization. One mitochondrial gene fragment (Cytochrome oxidase I) and one nuclear protein‐coding gene fragment (Wingless) were sequenced and the results compared with those of a detailed morphological study of the specimens from an extensive sampling. Knowledge of the biodiversity of Eupelmus in the Western Palearctic Region is significantly improved through the separation and description of 11 new species: E. (Eupelmus) confusus Al khatib sp.n., E. gemellus Al khatib sp.n., E. janstai Delvare & Gibson sp.n., E. longicalvus Al khatib & Fusu sp.n., E. minozonus Delvare sp.n., E. opacus Delvare sp.n., E. pistaciae Al khatib sp.n., E. priotoni Delvare sp.n., E. purpuricollis Fusu & Al khatib sp.n., E. simizonus Al khatib sp.n. and E. tremulae Delvare sp.n. Illustrated keys to females and, when known, males of these new 11 species plus the other already described species considered to belong to the 'urozonus‐complex' (E. acinellus Askew, E. annulatus Nees, E. azureus Ratzeburg, E. cerris Förster, E. fulvipes Förster, E. kiefferi De Stefani, E. martellii Masi, E. stenozonus Askew, E. tibicinis Bouček and E. urozonus Dalman) are provided and all the species are described based on morphology. Eupelmus kiefferi is removed from synonymy under E. urozonus and E. azureus is recognized as the valid senior synonym of Pteromalus cordairii Ratzeburg, 1844 and Eupelmus spongipartus Förster, 1860syn.n. The discrimination of the species included in this complex is particularly relevant because some are potential biological control agents and have been confused in the past. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:F52CD199‐C65F‐43CC‐B347‐4E724096F2D5.